2015
DOI: 10.1186/s13640-015-0071-8
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral image classification via contextual deep learning

Abstract: Because the reliability of feature for every pixel determines the accuracy of classification, it is important to design a specialized feature mining algorithm for hyperspectral image classification. We propose a feature learning algorithm, contextual deep learning, which is extremely effective for hyperspectral image classification. On the one hand, the learning-based feature extraction algorithm can characterize information better than the pre-defined feature extraction algorithm. On the other hand, spatial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(63 citation statements)
references
References 33 publications
0
63
0
Order By: Relevance
“…As detailed in 5, the 3D architecture is capable of reaching a 99% accuracy rate while only using 9% of the image pixel to train the network. The state of the art method detailed in [38] also deploys 9% of the dataset for training. However, this approach under-performs the proposed 3D architecture with a 98% accuracy level for about 20,000 trained parameters against our 99% accuracy level for less than 7,000 trained parameters.…”
Section: Computational Cost and Training Data Requirementsmentioning
confidence: 99%
“…As detailed in 5, the 3D architecture is capable of reaching a 99% accuracy rate while only using 9% of the image pixel to train the network. The state of the art method detailed in [38] also deploys 9% of the dataset for training. However, this approach under-performs the proposed 3D architecture with a 98% accuracy level for about 20,000 trained parameters against our 99% accuracy level for less than 7,000 trained parameters.…”
Section: Computational Cost and Training Data Requirementsmentioning
confidence: 99%
“…The aforementioned methods simply employ various manually-extracted spectral-spatial features to represent the pixels, which highly depends on experts' experience and is not general. In contrast, deep learning-based methods [21], [44], which can generate features automatically, have recently attracted increasing attention in hyperspectral image classification. The first attempt can be found in [20], where stacked autoencoder was utilized for high-level feature extraction.…”
Section: A Hyperspectral Image Classificationmentioning
confidence: 99%
“…Subsequently, Mou et al [18] first employed Recurrent Neural Network (RNN) for hyperspectral image classification. Besides, Ma et al [21] attempted to learn the spectral-spatial features via a deep learning architecture by fine-tuning the network via a supervised strategy. Recently, Convolutional Neural Network (CNN) has emerged as a powerful tool for hyperspectral image classification [22], [23], arXiv:1905.06133v1 [eess.IV] 14 May 2019 [24].…”
mentioning
confidence: 99%
“…The learned features are expected to be more discriminative for classification. In fact, spatial adjacent pixels usually share similar spectral characteristics and have the same label, and using spatial information can reduce the uncertainty of samples and suppress the salt-and-pepper noise of classification results [57]. Furthermore, recent studies have found that a higher layer of the deep hierarchical model produces increasingly abstract representations and is increasingly invariant to some transformations [58,59].…”
Section: Spectral-spatial Responsementioning
confidence: 99%